Evolution of pathogenicity in the Bacillus cereus group. - Didelot, X; Barker, M; Falush, D; Priest, F (2009)
The Bacillus cereus group of bacteria comprises soil-dwelling saprophytes but on occasion these bacteria can cause a wide range of diseases in humans, including food poisoning, systemic infections and highly lethal forms of anthrax. While anthrax is almost invariably caused by strains from a single evolutionary lineage, Bacillus anthracis, variation in the virulence properties of strains from other lineages has not been fully addressed. Using multi-locus sequence data from 667 strains, we reconstructed the evolutionary history of the B. cereus group in terms of both clonal inheritance and recombination. The strains included 155 clinical isolates representing B. anthracis, and isolates from emetic and diarrhoeal food poisoning, septicaemia and related infections, wound, and lung infections. We confirmed the existence of three major clades and found that clinical isolates of B. cereus (with the exception of emetic toxin-producing strains) are evenly distributed between and within clades 1 and 2. B. anthracis in particular and emetic toxin-producing B. cereus show more clonal structure and are restricted to clade 1. Our characterization of the patterns of genetic exchange showed that there exist partial barriers to gene flow between the three clades. The pathogenic strains do not exhibit atypically high or low rates of recombination, consistent with the opportunistic nature of most pathogenic infections. However, there have been a large number of recent imports in clade 1 of strains from external origins, which is indicative of an on-going shift in gene-flow boundaries for this clade.